Developing a dental leadership programme to address global oral health challenges. Issue 2 (12th March 2020) - Wordley, Valerie; Bedi, Raman
Abstract : Dental leadership is essential in addressing the crisis of 21st century dentistry. The Senior Dental Leaders programme was established in 2006 and has since influenced global oral health policy. The programme demonstrates how collaborative leadership and an engaged alumni network can produce successful dental leaders, significantly impacting upon child oral health around the world. There is now a great need for leadership development programmes at every level of dental training.